(untitled) (Journal of the College of Basic Education, 2022)
This study came to reveal the spatial distribution of educational services (kindergartens, primary, middle, preparatory and secondary schools) in the district of Rashidiya for the reality of the academic year (2020_2021). And at the district level, reviving them, and then knowing the efficiency and adequacy of the distribution of those services. Where it relied on a set of curricula in addition to the field study, including the descriptive approach, the fundamentalist approach, the regional approach, and the spatial quantitative approach. efficiency in all its stages.